Pharmacokinetic Interaction Between Favipiravir and Amlodipine in Hypertensive Local Rabbits (Oryctolagus cuniculus) - I Al-ameedi, Ali; M AL-Rekabi, Falah (The Iraqi Journal of Veterinary Medicine, 2023)
In the treatment of COVID-19, the antiviral medication Favipiravir has proven to be quite successful. Its metabolism is mediated by the enzymes aldehyde oxidase (AO) and xanthine oxidase (XO). This research investigated the potential drug-drug interaction betweenfavipiravir and amlodipine in hypertensive rabbits. Twenty local adult male rabbits (aged between 10 and 12 months and weighing between 2 and 2.5 kg) were induced with hypertension by 20 mg/kg BW of desoxycorticosterone acetate subcutaneously for three weeks and then divided randomly into two groups of ten. The first group received a single oral dose of 40 mg/kg BW of favipiravir, while the second group received 5 mg/kg of amlodipine orally for 14 consecutive days to inhibit AO before receiving a single oral dose of 40 mg/kg BW of favipiravir. Blood samples were collected from the marginal ear vein at 15, 30, 45 min, and 1, 2, 4, 8, 12, 24, 48, 36, 48, and 72 h. High-performance liquid chromatography (HPLC) was used to determine the concentration of favipiravir in the plasma. The results showed that co-administration of amlodipine prolonged the time taken for favipiravir (Tmax) to reach maximum plasma concentration (Cmax) and decreased its elimination half-life, while increasing the area under the curve (AUC). Amlodipine also prolonged the elimination of favipiravir by reducing the clearance per unit time (Cl/f). Additionally, hypertension potentiated the effect of amlodipine on the absorption, distribution, metabolism, and excretion of favipiravir. In conclusion, concomitant use of favipiravir with other drugs that affect AO enzyme activity may alter the pharmacokinetic profile of the drug. Therefore, adjusting the dose of favipiravir administered to hypertensive patients receiving amlodipine is recommended.